Difference In Multicultural Awareness and Multicultural Efficacy between Regular People of Multi-Cultural Backgrounds and North Korean Refugees, as Perceived by Nursing Students of South Korea (Medico Legal Update, 2019)
Background/Objectives: This study was conducted to identify the difference in multicultural awareness and multicultural efficacy between regular people of multi-cultural backgrounds and North Korean refugees, as perceived by nursing students.Method/Statistical Analysis: Data were collected using a total of 717 copies of a questionnaire. A frequency analysis, paired t-test, and Pearson’s correlation coefficients were used for the analysis.Finding: The analysis showed that the multicultural awareness of university students majoring in nursing, towards North Korean refugees was lower than the multicultural awareness they had towards regular people of multicultural backgrounds excluding North Korean refugees. In addition, both multicultural awareness and multicultural efficacy towards regular people and North Korean refugees had a positive correlation. This researcher suggests developing a program to promote multicultural capabilities in university students of nursing towards North Korean refugees.Improvements/Applications: This program would have to address the culture-specific awareness towards North Korean refugees in addition to general multicultural awareness.